Effect of short-term psychological intervention on anxiety of pregnant women with positive screening results for chromosomal disorders: a randomized controlled trial - Arezoo Bayat; Leila Amiri-Farahani; Mehdi Soleimani; Nooshin Eshraghi; Shima Haghani (BMC, 2021)
Abstract Background and aim Prenatal diagnosis of fetal abnormalities is a critical and stressful event for women. Most pregnant women are concerned about fetal abnormalities and screening tests. Due to the importance of anxiety reduction in pregnant women, this study was conducted to determine the effect of short-term psychological intervention on the anxiety of pregnant women with positive screening results for chromosomal disorders. Methods A randomized clinical trial was performed on women referred to Akbarabadi Hospital in Tehran, Iran, who had positive screening results for chromosomal abnormalities. Participants were selected from eligible individuals by a continuous method and were assigned to two groups of cognitive-behavioral training (n = 46) and control (n = 46), using the block balanced randomization method. Participants in the cognitive-behavioral training group received 4 sessions of individual counseling. The control group received routine pregnancy visits. The Spielberger State-Trait Anxiety Inventory was completed before the intervention and immediately at the end of the intervention (before receiving the amniocentesis result). The analysis of intervention effects was performed as intention-to-treat and per-protocol analysis. Results There was a statistically significant difference in post-intervention state anxiety scores and trait anxiety scores (p <  0.001) between the intervention and control groups, when their means were adjusted for pre-intervention scores for both intention-to-treat and per-protocol analysis. Also, there was a large effect size between the groups in terms of state (ITT: ηp 2 = 0.63, PP: ηp 2 = 0.71) and trait (ITT: ηp 2 = 0.72, PP: ηp 2 = 0.75) anxiety scores clinically for both intention-to-treat and per-protocol analysis. The intervention group had a statistically significant and large decrease in state and trait anxiety scores from pretrial to post-trial. In contrast, the control group had a statistically significant and medium increase in state and trait anxiety scores from pretrial to post-trial. Conclusion The results showed that cognitive-behavioral training reduced the anxiety of pregnant women with positive screening results for chromosomal disorders. According to the results, it is recommended to hold cognitive-behavioral training classes to reduce the anxiety of pregnant women with a positive screening result for chromosomal disorders. Trial registration IRCT.ir: IRCT20180427039436N7 ; date of registration: 24/08/2020 2020-08-24.